Married to a Marriage Therapist: An Insider Perspective. Issue 5 (19th October 2020) - Miller, Christine M.; Jackson, Jeffrey B.; Landers, Ashley L.
Abstract: Semi-structured interviews conducted with 14 spouses of licensed practicing marriage therapists were analyzed using descriptive phenomenology. Participants described benefits that their spouse's expertise had on their marriage; however, participants did not want their spouse to treat them like a client. Aspects of the spouse's career that spilled over into the marriage included infringements on time spent together, financial issues, and the confidential nature of clinical work. Most participants were uncertain as to whether aspects of their marriage were more influenced by their spouse's profession or their spouse's personality. Participants were proud and protective of their spouse's clinical work.